Genetic analysis of Rhipicephalus sanguineus sensu lato ticks, parasites of dogs in the Canary Islands, Cyprus, and Croatia, based on mitochondrial 16S rRNA gene sequences - Chitimia-Dobler, Lidia; Kurzrock, Lina; Molčányi, Tomáš; Rieß, Ramona; Mackenstedt, Ute; Nava, Santiago (Springer, 2019)
The aim of this work was to perform an analysis based on mtDNA sequences of the 16S rRNA gene in order to determine the phylogenetic position of ticks belonging to the Rhipicephalus sanguineus group from the Canary Islands, Cyprus, and Croatia. All the haplotypes obtained from ticks collected in the Canary Islands and Croatia grouped with R. sanguineus sensu stricto from France, Portugal, Italy, Switzerland, Argentina, Chile, Uruguay, and the USA. The sequences of R. sanguineus sensu lato from Cyprus formed a clade with R. sanguineus s.l. from Egypt, Turkey, and Romania, which belongs to the “Rhipicephalus sp. morphotype I” or “southeastern European lineage.” Ticks determined as R. turanicus s.l. from Cyprus clustered separately from the remaining clades of the R. sanguineus group, including R. turanicus s.s. The data show that R. sanguineus s.s. is present in the Canary Islands and Croatia, while R. sanguineus “southeastern lineage” is found in Cyprus.